The The Influence of Self-Sufficiency, Information Seeking, and Knowledge Towards Smart Purchasing Behavior in Indonesia - Azzara, Rana Chyntia; Simanjuntak, Megawati; Retnaningsih; Yandri (School of Business, Bogor Agricultural University (SB-IPB), 2023)
Smart purchasing behavior is a bright act of a consumer in deciding to use a product. Several studies show that consumer needs and desires contribute to purchasing behavior. This study aimed to analyze the influences of self-sufficiency, information seeking, and knowledge on smart purchasing behavior in Indonesia. There were 2100 married or working respondents with an age range of 17-60 years from which several data were generated, including self-sufficiency, information seeking, knowledge, and smart purchasing behavior. Data analysis applied Structural Equation Modelling using LISREL 8.7. The findings showed that self-sufficiency significantly influenced information seeking. Moreover, a significant positive correlation was evident between information-seeking, knowledge, and smart purchasing behavior. Governments and consumer protection institutions need to increase the quantity and quality of socialization to improve the perspective of consumer knowledge and smart purchasing behavior. Keywords: information seeking, knowledge, self-sufficiency, smart purchasing behavior, SEM